Femoral Nerve Block after Anterior Cruciate Ligament Reconstruction - Magnussen, Robert A.; Pottkotter, Kristy; Stasi, Stephanie Di; Paterno, Mark V.; Wordeman, Samuel C.; Schmitt, Laura C.; Flanigan, David C.; Kaeding, Christopher C.; Hewett, Timothy E. (The Journal of Knee Surgery, 2017)
Femoral nerve block (FNB) has been proposed for pain control following anterior cruciate ligament (ACL) reconstruction. Although numerous studies have assessed the efficacy of FNBs, there has been little to no research into the effect of such blocks on postoperative strength and patient-reported outcomes. We hypothesized that performance of an FNB would result in decreased quadriceps strength and poorer patient-reported outcome scores within the first 6 months following ACL reconstruction. A total of 30 patients scheduled to undergo hamstring autograft ACL reconstruction following an acute ACL injury were randomized to a single-shot FNB group or a control group. Preoperatively, patients completed a Knee Injury and Osteoarthritis Outcome Score (KOOS) and isokinetic quadriceps strength testing at 60 degrees/second. At 6 weeks postoperative, 29 of 30 patients completed a KOOS and isometric quadriceps strength testing at 90 degrees. At 6 months postoperative, 23 of 30 patients completed a KOOS and isokinetic strength testing. Quadriceps femoris strength limb symmetry indices (QF-LSI) were calculated at all time points. Repeated measures analysis of variance (ANOVA) models were then utilized to model the effect of FNB and time on QF-LSI as well as KOOS subscales for activities of daily living, pain, and symptoms. QF-LSI and all KOOS subscales demonstrated improvement with time following ACL reconstruction. Repeated measures ANOVA demonstrated that patients who underwent FNB had a mean QF-LSI that was 13.4% lower than the control group (p = 0.005) and poorer KOOS symptoms subscale scores (10.4 point difference, p = 0.032) at 6 weeks postoperative compared with controls. At 6 months postoperative, no differences were noted in QF-LSI or any of the KOOS subscales based on block status. FNB resulted in decreased strength and poorer KOOS symptom subscale score at 6 weeks following ACL reconstruction compared with controls. These differences resolved by 6 months postoperative. The long-term effect of delayed quadriceps recovery on movement patterns and functional outcome remains unknown and requires further study. The study is a randomized controlled trial with level of evidence 1.
Keywords: anterior cruciate ligament reconstruction; femoral nerve block; patient-reported outcomes; strength testing